2021
DOI: 10.1016/s2214-109x(21)00176-5
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of infectious and non-communicable disease epidemics in rural South Africa: a cross-sectional, population-based multimorbidity study

Abstract: Summary Background There has been remarkable progress in the treatment of HIV throughout sub-Saharan Africa, but there are few data on the prevalence and overlap of other significant causes of disease in HIV endemic populations. Our aim was to identify the prevalence and overlap of infectious and non-communicable diseases in such a population in rural South Africa. Methods We did a cross-sectional study of eligible adolescents and adults from the Africa Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 33 publications
5
83
0
Order By: Relevance
“…Our study noted attrition at all stages of the HCC. The gaps in diagnosis, treatment and control are consistent with studies conducted in rural South Africa ( Addo, Smeeth & Leon, 2007 ; Adeniyi et al, 2016 ; Siedner et al, 2018 ; Wong et al, 2021 ). Hypertension care cascade gaps in South Africa have been attributed to long distances to health centres, poor health-seeking behaviour and perceived low quality of services, including lengthy waiting periods ( Nulu, Aronow & Frishman, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study noted attrition at all stages of the HCC. The gaps in diagnosis, treatment and control are consistent with studies conducted in rural South Africa ( Addo, Smeeth & Leon, 2007 ; Adeniyi et al, 2016 ; Siedner et al, 2018 ; Wong et al, 2021 ). Hypertension care cascade gaps in South Africa have been attributed to long distances to health centres, poor health-seeking behaviour and perceived low quality of services, including lengthy waiting periods ( Nulu, Aronow & Frishman, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…Although healthcare services are publicly provided, transport costs hinder the utilisation of healthcare services in rural KwaZulu-Natal ( Chimbindi et al, 2015 ). UMkhanyakude district has a high prevalence of communicable and noncommunicable diseases ( Sharman & Bachmann, 2019 ; Wong et al, 2021 ), and in mid-2021, it was among the districts with the least cumulative cases (11,548) and fatalities (422) of COVID-19 in KwaZulu-Natal province ( KZN_Department_of_Health, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the highest prevalence worldwide for both infectious diseases and non-communicable diseases (NCDs), as well as patients with multiple co-morbidities, including both infectious and non-infectious diseases, is found in Africa [ 1 , 2 , 3 , 4 , 5 , 6 ]. The prevention and management of these patients, especially those with multiple co-morbidities, will require an improved understanding of the causal determinants of individual and overlapping diseases, including potential genetic factors [ 7 ]. Alongside this, there can be co-payment issues in a number of African countries, which can also have catastrophic consequences on patients and their families [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate training of physicians and pharmacists is essential to deal with increasingly complex cases across Africa given the increasing prevalence of diseases and patients with co-morbidities [ 7 , 52 , 53 , 54 , 55 ]. This is seen as particularly important during the COVID-19 pandemic given the extent of misinformation that exists regarding possible medicines for the prevention and treatment of COVID-19 and their consequences [ 9 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decade prior, researchers were predicting the negative impacts associated with the collision of these two epidemics in South Africa [ 9 ]. More recently, studies have found a high and overlapping prevalence of disease conditions such as HIV, tuberculosis and NCDs in both community settings [ 10 , 11 , 12 ] and health facilities in the country [ 13 ].…”
Section: Introductionmentioning
confidence: 99%